An update on the current salt content of Portuguese processed foods - Albuquerque, T.G. (2018)
The Portuguese HYpertension and SAlt (PHYSA) study, conducted in 2013, revealed that the Portuguese population has an average salt intake of 10.3 g/day, which is more than the double of WHO recommendations.